2021
DOI: 10.1007/s00170-021-07431-6
|View full text |Cite|
|
Sign up to set email alerts
|

Design of an innovative new extrusion system for a printing machine for ceramics

Abstract: Today, the introduction of ceramic materials in the medical eld is becoming a vital necessity because of its stable physicochemical characteristics, high biocompatibility, and good osteoconductivity. On the other hand, machining of ceramic components is di cult, owing to their extreme hardness and brittleness. Additive Manufacturing (AM) technologies are an appropriate alternative to obtain the complex shapes of implants, which can have porous structures. Thus, since the development of 3D printing, Direct Ink … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The extruder can be integrated into a conventional Cartesian 3D printer, thus aiding to the spread of low cost DIW printers in materials research labs. Similar to this study, numerous researchers have proposed extruders that signi cantly reduce the price of commercial DIW devices [11][12][13][14][15]. The challenge in this case is that, in addition to cost reduction, we look for the combination in one device of the functional advantages presented separately in those works, including capacity for multiple syringe volumes and multimaterial printing, ease of assembly, compatibility with most commercial FDM printers, ow control, retraction control, and the ability to extrude inks with a wide range of viscosities.…”
Section: Introductionmentioning
confidence: 53%
“…The extruder can be integrated into a conventional Cartesian 3D printer, thus aiding to the spread of low cost DIW printers in materials research labs. Similar to this study, numerous researchers have proposed extruders that signi cantly reduce the price of commercial DIW devices [11][12][13][14][15]. The challenge in this case is that, in addition to cost reduction, we look for the combination in one device of the functional advantages presented separately in those works, including capacity for multiple syringe volumes and multimaterial printing, ease of assembly, compatibility with most commercial FDM printers, ow control, retraction control, and the ability to extrude inks with a wide range of viscosities.…”
Section: Introductionmentioning
confidence: 53%
“…Xi et al [14] identified machining features using the extended adjacency matrix method, customizing typical feature machining templates, and realizing automatic programming for spacecraft cabin segment parts. Abdelilah et al [15] decoded geometric and topological information from STEP files and reconstructed machining features, defining manufacturing parameters, machining strategies, and cutting tools to achieve automated turning machining processes.…”
Section: Introductionmentioning
confidence: 99%